2011
DOI: 10.2119/molmed.2011.00080
|View full text |Cite
|
Sign up to set email alerts
|

All-trans Retinoic Acid Upregulates Reduced CD38 Transcription in Lymphoblastoid Cell Lines from Autism Spectrum Disorder

Abstract: Deficits in social behavior in mice lacking the CD38 gene have been attributed to impaired secretion of oxytocin. In humans, similar deficits in social behavior are associated with autistic spectrum disorder (ASD), for which genetic variants of CD38 have been pinpointed as provisional risk factors. We sought to explore, in an in vitro model, the feasibility of the theory that restoring the level of CD38 in ASD patients could be of potential clinical benefit. CD38 transcription is highly sensitive to several cy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
41
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 67 publications
(42 citation statements)
references
References 49 publications
1
41
0
Order By: Relevance
“…Correspondingly, any potential therapeutic effect of OT on social functioning in ASD is only partially mediated by the reported imaging phenotype or the underlying genotype. Apart from these constraints, very recently it has been shown that retinoids can be used to increase CD38 expression (Riebold et al, 2011) implicating a direct method to influence the CD38 system and related social cognitive deficits in autism (Ebstein et al, 2011). Finally, in this context, our findings indicate that one should take into account the individual genetic makeup when evaluating treatment effects.…”
Section: Discussionmentioning
confidence: 73%
“…Correspondingly, any potential therapeutic effect of OT on social functioning in ASD is only partially mediated by the reported imaging phenotype or the underlying genotype. Apart from these constraints, very recently it has been shown that retinoids can be used to increase CD38 expression (Riebold et al, 2011) implicating a direct method to influence the CD38 system and related social cognitive deficits in autism (Ebstein et al, 2011). Finally, in this context, our findings indicate that one should take into account the individual genetic makeup when evaluating treatment effects.…”
Section: Discussionmentioning
confidence: 73%
“…It has been shown that SNPs of CD38 are associated with ASD [5762]. As CD157 is abundant in the embryonic stages, speculation regarding an association between the SNPs of CD157 and ASD is understandable.…”
Section: Discussionmentioning
confidence: 99%
“…When children were 3 years old, parents' and child's salivary OT was measured and children's social reciprocity was assessed during interactions with mother, father, and their first 'best friend'. We selected SNPs on the OXTR and CD38 genes that have been linked with increased risk for disorders involving severe social dysfunction, including autism and major depression (Costa et al, 2009;Lerer et al, 2008, 2010, Riebold et al, 2011. Three hypotheses were proposed.…”
Section: Introductionmentioning
confidence: 99%